The Influence of Sedimentation on Sump Capacity and Settling Pond at Pit East PT Unggul Dinamika Utama Kutai Timur Regency East Kalimantan Province: Pengaruh Sedimentasi Terhadap Kapasitas - Adillah, Resti; Shalaho D. Devy; Rety Winonazada; Revia Oktaviani; Agus Winarno (ReTII, 2025)
This research aims to determine the appropriate capacity for sump and settling pond by taking into account the sedimentation that occurs due to erosion carried by runoff water in the pit East of PT. Unggul Dinamik Utama. This analysis was conducted to avoid overflow that could disrupt activities in the mine opening. The results of the analysis show that the total sedimentation in the sump is 0.00000175 m3/day and in the settling pond is 3.10000114 m3/day. With this sedimentation calculation, the appropriate capacity for the sump is 85,523.79 m3 and the settling pond is 174,681.03 m3. Then from the sedimentation, mud material will be dredged referring to the technical instructions of Ministerial Decree No. 18227 K/30/MEM/2018 so that in the sump, dredging of settled mud material is carried out every 81 days, for settling pond in compartment 1 every 155 days, in compartment 2 every 62 days, in compartment 3 every 37 days, in compartment 4 every 49 days, in compartment 5 every 32 days, in compartment 6 every 18 days and retention pond every 6 days.